Plural ecologies in Southeast Asia: hierarchies, conflicts, and coexistence - Duile, Timo; Großmann, Kristina; Haug, Michaela; Sprenger, Guido (Routledge, 2023)
"This book draws on ethnographic studies in Southeast Asia to provide new insights into human-environmental relationships and ecologies, together with a set of theoretical innovations. Contextualizing ecologies in this region as pluralizing or hegemonic, conflictive or cooperative, the case studies in these chapters bring into dialogue ontological approaches, the issue of distinct worldviews and concepts of nature on the one hand and political ecology and power relations on the other. They discuss plural ecologies in diverse settings, reaching from urban Vietnam to the Javanese coast and the dense forests of the Southeast Asian highlands. Southeast Asia is one of the most biodiverse and culturally diverse regions in the world. Thus, what occurs in this region is vitally important to the future of Earth. Documenting the plurality and dynamics of ecologies in Southeast Asia, this book provides prime examples for the potentials of alternative human-environmental relationships and sustainable development. It will be of interest to academics studying political ecology, environmental anthropology, sustainability sciences, political sciences, development studies, human geography, human ecology, Southeast Asian studies, and Asian studies"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Ethnologie; Umwelt; Mensch; Südostasien; Nachhaltigkeit; Humanökologie